PENINGKATAN KETERAMPILAN MENGAJAR GURU MI DALAM ERA DIGITAL - lestari, hana; Rahmawati, Ima (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
The enhancement of teaching skills among teachers at Madrasah Ibtidaiyah (MI) Ibnu Sina Pamijahan Bogor in the digital era is crucial for ensuring relevant and effective educational quality. This study aims to analyze teachers' needs, design, and implement a training program focused on integrating technology into learning. The implementation method consists of six steps: needs analysis, program design, training execution, evaluation, community of practice formation, and monitoring and assessment. The needs analysis revealed that the majority of teachers felt insecure about using technology, prompting the training program to focus on improving skills in utilizing educational software, interactive teaching techniques, and virtual classroom management. The training was conducted through both face-to-face and online sessions, receiving positive feedback from participants, with 85% of teachers finding the training highly beneficial. Evaluation indicated significant improvements in the application of technology in teaching, as well as increased student motivation and engagement. The community of practice formed post-training served as a sustainable support system, enhancing collaboration among teachers. Monitoring six months after the training showed that 75% of teachers remained active in using technology, with improved student learning outcomes. These findings suggest that enhancing teaching skills in a digital context benefits not only the teachers but also significantly elevates the overall quality of education, which is essential for addressing future educational challenges.